TRANSFORMASI BENTUK MAKAM RAJA-RAJA TANETE DARI ABAD KE-17 HINGGA ABAD KE-20 - Muhammad Nur (WalennaE, 2018)
Our understanding of the cultural transformation phase of the Islamic grave in South Sulawesi is still limited to the study of its territorial scope, not specific to a particular locality or kingdom. This study aims to determine the stage of transformation of Islamic shape tomb in Tanete Kingdom, Barru and its causal factors. The research used artefactual data which are four complex of King Tanete tomb, interview data and historical data. The methods used are survey, interview, literature study, identification, and interpretation. The study concludes three stages of transformation shape tomb at Tanete, the first transformation of the early seventeenth century characterized by tombstone, both occurring in the mid-18th century to the beginning of the nineteenth century characterized by decorative and inscribed tombs, and the third occurred beginning of the 20th century with the characteristic of European architecture. The cause of the three stages of the transformation of the tomb is the external factor, the first stage of the Gowa kingdom, the second stage of Malay culture, and the third stage is the influence of political relations with the Dutch Government. Pemahaman kita tentang fase transformasi budaya kubur Islam di Sulawesi Selatan masih terbatas pada kajian yang sifatnya wilayah, belum spesifik pada satu lokalitas atau kerajaan tertentu. Penelitian ini bertujuan mengetahui tahapan tranformasi bentuk makam Islam di Kerajaan Tanete, Barru dan faktor penyebabnya. Data yang digunakan adalah data artefaktual yaitu empat kompleks makam Raja Tanete, data wawancara dan data sejarah. Metode yang digunakan adalah survei, wawancara, studi literatur, identifikasi dan interpretasi. Penelitian ini menyimpulkan tiga tahap transformasi bentuk makam di Tanete, transformasi pertama pada awal abad ke-17 yang dicirikan oleh makam bercungkup, kedua terjadi pada pertengahan abad ke-18 hingga awal abad ke-19 yang dicirikan oleh makam dekoratif dan berinskripsi, dan ketiga terjadi awal abad ke-20 dengan ciri arsitektur Eropa. Penyebab tiga tahap transformasi bentuk makam tersebut adalah faktor eksternal, tahap pertama dari kerajaan Gowa, tahap kedua dari budaya Melayu, dan tahap ketiga adalah pengaruh hubungan politik dengan Pemerintah Belanda.